2010
DOI: 10.1590/s0001-37652010000400018
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and symptoms analysis in Mexican patients with irritable Bowel syndrome, dyspepsia, and gastroesophageal reflux disease

Abstract: The aim of this study was to analyze the data of endoscopy and symptoms in 118 Mexican patients with irritable bowel syndrome (IBS), dyspepsia, non-erosive reflux disease (NERD) and erosive esophagitis (EE). IBS criteria were fulfilling for dyspepsia patients in 47%, for NERD in 48%, and for EE patients in 48% of cases. Esophagitis was present in 42% of patients with IBS and in 45% of patients with dyspepsia. A higher prevalence of hiatus hernia was found in EE vs. NERD. Heartburn and acid eructation were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Out of this large pool, only 50 studies met our inclusion criteria with a focus on patients with reflux symptoms and provided sufficient information about sex distribution (Table 4). Twenty-five of the reports originated in Asia [37,, nine in Europe [99][100][101][102][103][104][105][106], seven in the US [56,[107][108][109][110][111][112], two in South America [113][114][115][116], four in African countries [117,118], and one in Canada [15], the studies reported data on 121 267 patients with 50.0 ± 1.2% women (range: 14.7-76.1%; P = 0.45). Considering the more recent emphasis of symptoms rather than endoscopic findings in the definition of GER, we examined time trends by separating studies into 3-year blocks, on the basis of their year of publication.…”
Section: Sex and Endoscopic Findings: Patient Studiesmentioning
confidence: 99%
“…Out of this large pool, only 50 studies met our inclusion criteria with a focus on patients with reflux symptoms and provided sufficient information about sex distribution (Table 4). Twenty-five of the reports originated in Asia [37,, nine in Europe [99][100][101][102][103][104][105][106], seven in the US [56,[107][108][109][110][111][112], two in South America [113][114][115][116], four in African countries [117,118], and one in Canada [15], the studies reported data on 121 267 patients with 50.0 ± 1.2% women (range: 14.7-76.1%; P = 0.45). Considering the more recent emphasis of symptoms rather than endoscopic findings in the definition of GER, we examined time trends by separating studies into 3-year blocks, on the basis of their year of publication.…”
Section: Sex and Endoscopic Findings: Patient Studiesmentioning
confidence: 99%
“…The authors concluded that the presence of these disorders might explain why many patients with GERD have no complete symptom relief with PPI treatment. In 118 Mexican patients with IBS (Rome I criteria), Camacho et al [ 53 ] showed a general prevalence of IBS symptoms (48%) in patients with ERD and NERD. In a group of ERD (286) and NERD (74) patients from South Korea, Noh et al [ 54 ] described a prevalence of IBS (Rome III criteria) of 10.1%.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore a very popular tool for analysing data that arise in many scientific disciplines, for instance biology (e.g., Soares et al 2011, Juliá and Peris 2010, Camargo et al 2011, biomedical and medical sciences (e.g., Camacho et al 2010, Oliboni et al 2011, earth sciences (e.g., Fontana et al 2010, Rangel et al 2011, social sciences (e.g., Conte et al 2011), economics (e.g., Misztal 2011), ergonomics (e.g., Bin andRichardson 2010, Zadry et al 2011), and of course agriculture (e.g., Chełkowski et al 2000, Cheng et al 2010, Lakhesar et al 2010, Bandehagh and Hossein Zadeh Moghbeli 2011, Cherati et al 2011, Heidari Zooleh et al 2011, Herrero et al 2011, Kesavacharyulu et al 2011, Rogiers et al 2011.…”
Section: Introductionmentioning
confidence: 99%